AN INVESTIGATION INTO THE STRUCTURE OF THEME AND RHEME IN ENGLISH AND VIETNAMESE POLITICAL SPEECHES - Assoc. Prof. Dr. Phan Văn Hòa (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2025)
This paper is aimed to study the Structure of Theme- Rheme in English and Vietnamese political speeches in comparison to each other, their characteristics, and semantic, pragmatic aspects.